Highly Compact GCPW-Fed Multi-Branch Structure Multi-Band Antenna for Wireless Applications - Ikhlas Ahmad; Wasi Ur Rehman Khan; Sadiq Ullah; Naveed Mufti; Abdullah G. Alharbi; Niamat Hussain; Mohammad Alibakhshikenari; Mariana Dalarsson (International Journal of Antennas and Propagation)
In this work, we present a highly compact multi-branch structure multi-band antenna with a grounded coplanar waveguide (GCPW)-fed structure printed on 26 × 13 × 1.6 mm3 sized FR-4 substrate having dielectric constant εr of 4.3 and loss tangent δ of 0.02. In the proposed antenna, five branches are extended from the main radiator to provide multi-band behavior. Two branches are introduced at the upper end of the main radiator, effectively covering the lower bands, while the other three branches are introduced near the center of the main radiator to extend operation to higher bands. The designed antenna covers five different bands: 2.4 GHz, 4.5 GHz, 5.5 GHz, 6.5 GHz, and 7.8 GHz, with respective gain values of 1.34, 1.60, 1.83, 1.80, and 3.50 dBi and respective radiation efficiency values of 90, 88, 84, 75, and 89%. The antenna shows a good impedance bandwidth, ranging from 170 MHz to 3070 MHz. The proposed antenna is simulated in CST Microwave Studio, while its performance is experimentally validated by the fabrication and testing process. The antenna has potential applications for IoT, sub-6 GHz 5G and WLAN (both enablers for IoT), C-band, and X-band services.